Identification of Leaching Zone in Pasirimpun Dump Station, West Java, Indonesia Using Resistivity and Induced Polarization Method - Alfin Ari Nugraha; A.` A. Ilmanto; J. Jonathan; R. M. Rashad; S. Maghrifa (Himpunan Ahli Geofisika Indonesia (HAGI), 2018)
The presence of dump stations around resident's houses besides resulting air pollution, it is also affectingthe cleanliness of water used by society to meet their daily needs. Location where we researched is at ex-Pasirimpun Dump Station, Karang Pamulang Village, Kecamatan Cicadas, Bandung. Although Pasirimpun Dump Station has been closed and turned function into Taman Abdi Negara, it is feared that there is a water pollution caused by leach zone. Geophysical measurements by geoelectric method are performed to prove the leaching zone. This study aims to determine the depth of the leaching zone, its position against the groundwater level, and what potential harm can caused by the leaching zone. The methodology that is used are direct observation, interviews, and literature studies. Our measurements is done by using schlumberger conguration and Induced Polarization (IP) method on morphology that tend to be at with a length of 141 meters stretch and a spaceof 3 meters. Groundwater faces are mapped to be correlated with the depth of the existing leaching zone. From the results of literature studies, there is a leaching zone in the area with a depth of about 30 meters. By knowing this leaching zone, we hope that there will be cooperation between government and society to avoidthe impacts of leaching zone on the water which they consumed. One way to know, is to drill deeper water level from the leach zone.